FDI inflows and poverty reduction in Botswana: An empirical investigation - M. T. Magombeyi; N. M. Odhiambo (Cogent Economics & Finance, 2018)
This study investigates the impact of foreign direct investment (FDI) inflows on poverty reduction in Botswana from 1980 to 2014. The main objective of this study is to establish whether FDI plays a positive role in poverty reduction. The study employs autoregressive distributed lag (ARDL) bounds test approach to co-integration and the error correction model to investigate the relationship. To ensure robustness, the study uses three poverty reduction proxies which are household consumption expenditure (Pov1), infant mortality rate (Pov2), and life expectancy (Pov3). The findings from this study revealed that FDI has a positive impact on poverty reduction in the short run and a negative impact in the long run when life expectancy is used as a poverty reduction measure. When infant mortality rate is used as a poverty reduction proxy, an insignificant relationship is registered in both the long run and the short run. A negative impact of FDI on poverty reduction is confirmed in the short run when household consumption expenditure is used as a poverty reduction proxy, while in the long run an insignificant relationship is reported. The study concludes that the impact of FDI on poverty reduction is sensitive to the poverty reduction proxy used.
Keywords: F21; I32; 330; Botswana; poverty reduction; foreign direct investment; household consumption expenditure; infant mortality rate; life expectancy; autoregressive distributed lag